Structural Optimization of Simple Span Bridge by Adding Truss Structure - Koirala, Robin; Acharya, Ananta; Chitrakar, Sailesh (Kathmandu University Journal of Science Engineering and Technology, 2021)
A truss is a structure that involves members assembled into connecting triangles so that the overall connection behaves as a single object. Its application is in industrial and building construction. This paper presents a study about optimizing a simple span bridge in terms of stress, the factor of safety, and maximum displacement by adding different structures. A simple span bridge having a span length of 12m was modeled using SolidWorks’s finite element analysis approach. A uniform initial load of 5000N was applied to the beams in all cases to determine safety factors, which helps determine the maximum allowable force, the maximum displacement, and the ultimate yield stress. The result shows that a simple span bridge has an efficiency score, the maximum displacement of 24.17, and 749.9 mm, respectively. Upon design modification by adding Howe truss structure, floor beams, and lateral bracing, a considerable increase in efficiency score was observed with reduced displacement. Among all cases, the optimized bridge has an efficiency score and maximum displacement of 83.69 and 63.08 mm, respectively. This paper aims to find the optimized structure to its full capacity for the given material.